(untitled) - Stein, R. Conrad; Canaday, Ralph (Childrens Press, 1981)
Discusses the network of groups and individuals throughout Ohio and the New England states who aided slaves escaping from their captivity during the nineteenth century.
Keywords: Slavery; Underground railroad; Juvenile literature; Anti-slavery movements; United States; Underground railroad; Slavery; Anti-slavery movements; Slavery in the United States